2014
DOI: 10.3329/sja.v11i1.18388
|View full text |Cite
|
Sign up to set email alerts
|

Zinc fertilization effects on agromorphological and quality parameters of commonly grown rice

Abstract: Among the micronutrients, zinc deficiency is widespread throughout the world particularly in low land rice fields causing low yields and affecting nutritional quality of the produce. In present investigation, 26 rice cultivars including some locals, aromatics, HYVs and hybrids grown on an Inceptisols with no Zn, basal Zn and soil+foliar applied Zn were evaluated for agro-morphological and quality parameters in a strip plot design having three replications during kharif season for consecutive two years (2009 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Inglongkiri showed higher value of zinc content in brown rice over other varieties. This might be due to the differences in growth parameters of the cultivars (Senasdhira and Graham, 1999;and Saha et al, 2013) and also the genetic make-up of the variety which might have helped in better uptake and transportation into the grains.…”
Section: Resultsmentioning
confidence: 99%
“…Inglongkiri showed higher value of zinc content in brown rice over other varieties. This might be due to the differences in growth parameters of the cultivars (Senasdhira and Graham, 1999;and Saha et al, 2013) and also the genetic make-up of the variety which might have helped in better uptake and transportation into the grains.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of a negative relationship between irrigation and iron and zinc uptake (Scagel et al, 2012) and a similar negative relationship between phosphorus and iron and zinc uptake (Saha et al, 2013) also lead to lower the accumulation of these micronutrients in the cereal grains. Since the edible parts of the cereals are poor in iron and zinc, thus heavy dependence of people from developing countries on these foods results in the development of large-scale iron and zinc malnutrition.…”
Section: Issn: 2319-7706 Volume 7 Number 01 (2018)mentioning
confidence: 99%
“…Zinc take part in carbonic activity. Carbonic activity and more carbohydrate accumulation increase test weight (Saha et al 2013). Ghasemi et al (2013) reported application of zinc fertilizer in rice increased TGW over no application of zinc.…”
Section: Discussionmentioning
confidence: 97%